Partai Keadilan Sejahtera: A Mawdudian-Meliorist Vision of Islamism in Post-New Order Indonesia - Masdar Hilmy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
This article seeks to analyze how one group, that is, the Justice and Welfare Party (PKS), is attempting to clean up politics from within the political party system. This article argues that the existence of PKS has given a new but unique political nuance to the political party system in post-New Order Indonesia. The seemingly sudden rise of PKS has taken many by surprise, and it is for this that the party has become the topic of much discourse amongst scholars of Indonesia.DOI: 10.15408/sdi.v14i1.555